RETRACTED: Prevalence of pulmonary hypertension and its associated factors among chronic obstructive pulmonary diseases patients at public hospitals of Addis Ababa, Ethiopia, 2024: a facility-based cross-sectional study - Kasse, Tsehaynew; Elias, Amanuel; Lonsako, Arega Abebe; Agegnehu, Yalemzer (Frontiers in Public Health, 2024)
BackgroundPulmonary hypertension (PH) is a serious medical condition characterized by elevated pressure in the lung blood vessels, with chronic heart and lung diseases being the most common causes worldwide. However, there is a dearth of studies on the prevalence of pulmonary hypertension and its associated factors among chronic obstructive pulmonary disease (COPD) patients in Ethiopia and the study area.ObjectiveThis study aimed to assess the prevalence of pulmonary hypertension and its associated factors among patients with chronic obstructive pulmonary disease at public hospitals in Addis Ababa, Ethiopia, 2024.MethodsA facility-based cross-sectional study involving 422 COPD patients charted in Addis Ababa town, Ethiopia from May – June 2024 was conducted. Respondents’ records were chosen using simple random numbers. Structured, and pretested questionnaires, were used to collect data. The data were coded and entered into EpiData 3.1 before being exported to SPSS version 25 for analysis. Logistic regression was employed to identify factors influencing the prevalence of pulmonary hypertension. Statistical significance was set at p < 0.05 with a 95% confidence interval.ResultsThe study found the prevalence of pulmonary hypertension was 52% (95% CI: 49, 54.4%). Aged above 55 years [Adjusted Odds Ratio (AOR): 2.45 (1.55–3.9), Being male (AOR): 2.5 (1.5–4.1)]. Furthermore, having a history of alcohol [(AOR): 5.5 (2.4–13)], a history of smoking [(AOR): 4.6 (2.7–7.8), and congestive heart failure (AOR): 2.65 (1.5–4.6)], all increase the likelihood of pulmonary hypertension.ConclusionThe study revealed a higher prevalence of pulmonary hypertension among COPD patients. Significant associations were found with being male, belonging to an older age group, and having a history of alcohol use, smoking, and congestive heart disease. Implementing screening programs, smoking cessation programs, educational initiatives, and counseling patients on lifestyle modifications were recommended.